The Influence of Production Value and Investment on Labor Absorption in the Industrial Sector in East Java Province 2015-2024 - Mohamad Fathur Rohman; Anang Rohmad Jatimiko; Aqida Septaning Ayu (Jurnal Ragam Pengabdian, 2026)
This study analyzes the influence of production value and investment on labor absorption in the industrial sector in East Java Province during the period 2015-2024. The manufacturing industry sector is a major pillar for the economy in East Java which is expected to absorb a large number of workers to reduce unemployment. This study aims to analyze the influence of production value and investment on labor absorption in the industrial sector in East Java Province. The data used are secondary data sourced from the Central Statistics Agency of East Java Province with a sample size taken from 32 regencies and cities. The analysis method uses a quantitative approach using Statistical Product and Service Solutions (SPSS) software version 2025. The results of the study, conducted through partial tests, indicate that production and investment values have a positive and significant effect on labor absorption in East Java Province. Simultaneously, it was revealed that production and investment values together have a positive and significant effect on labor absorption. The implications of this study indicate that increasing production and investment values play a significant role in job creation. Therefore, production and investment value policies need to be considered and maintained to prevent labor absorption. The limitations of this study are the limited variables and the sample data period